2016
DOI: 10.1007/s00592-016-0911-8
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac dysfunction in type II diabetes: a bittersweet, weighty problem, or both?

Abstract: Aims Weight loss in obese patients leads to improved left ventricular (LV) function. It is unclear whether improving glycaemic control has additional benefits to weight loss alone in patients with type 2 diabetes, or if benefits of weight loss are mediated through improving glycaemic control. This case–control study examined the incremental impact of these approaches on LV function. MethodsThree groups of age, gender, and baseline HbA1c-matched patients with type 2 diabetes and suboptimal glycaemic control wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Therefore, 102 studies were reviewed; of these, 77 did not report data on myocardial mechanics, and 24 were reviews, commentary, editorial articles, case reports and studies including less than 10 participants. Thus, a total of 13 studies including patients treated with bariatric surgery for a period longer than one month and containing echocardiographic data of interest were included in the final review [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] ( Figure 1 ). According to the NOS, the quality of the studies ranged from 6 to 9 (i.e., a score that identifies studies of fair or good quality) [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, 102 studies were reviewed; of these, 77 did not report data on myocardial mechanics, and 24 were reviews, commentary, editorial articles, case reports and studies including less than 10 participants. Thus, a total of 13 studies including patients treated with bariatric surgery for a period longer than one month and containing echocardiographic data of interest were included in the final review [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] ( Figure 1 ). According to the NOS, the quality of the studies ranged from 6 to 9 (i.e., a score that identifies studies of fair or good quality) [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies outline the importance of weight loss in the reversibility of systolic and diastolic dysfunctions in DM patients 42,65,66 . M. Leung et al found that weight loss in type 2 DM was as important as glycaemic control for the improvement of systolic and diastolic function, the improvement being even greater when both glycaemic control and weight loss were obtained 65 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Lorenzo‐Almoros et al showed that intensive glycaemic control in humans (HbA1c < 7%) does not prevent cardiovascular complications in patients suffering from DM, 1 and several other studies found no association between HbA1c levels and systolic dysfunction 8,64 . However, many recent studies found that the biggest improvements in diastolic and systolic functions were seen in patients with the largest reduction in HbA1c levels 2,5,18,25,33,43,65 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in patients without concomitant disease such as HT and CAD, followed up for 6 years, the authors reported that the prevalence of LVDD was relatively low, suggesting that in the early stage of LVDD, there may be a slow progression of myocardial changes (26). Duration of diabetes, age and abnormally elevated levels of Hb1AC were independently correlated with LVDD in several studies (15,21,27,28,29). An independent relationship between LVDD and BMI was also reported (18,22,28).…”
Section: Epidemiologic and Clinical Aspectsmentioning
confidence: 94%